Substance use prevalence and outcomes in a psychiatric outpatient population in Southern Gauteng - Mokwatsi, Maria Lerato (My University, 2020)
Background: Substance use disorders (SUD) are commonly comorbid with mental illness and worsen outcomes of psychiatric care. Prevalence rates of 40% and 51% have been found for SUDs among psychiatric inpatients in South Africa. Aim: To ascertain the prevalence of SUD in a community psychiatric setting and its impact on care outcomes. Method: A retrospective record review was conducted at a community psychiatric clinic in Southern Gauteng. Results: Of the 368 records included, a SUD was recorded in 45.4% (n=167). Having a SUD was associated with being of a younger age (p<0.0001), male (p<0.0001), single (p<0.0001), having a higher level of education (p<0.0001), and a diagnosis of Schizophrenia (p<0.0001). Regarding care outcomes, SUD was associated with more missed clinic appointments (p<0.0001), more hospital adir issions (p<0.000) ), and a longer duration of hospital stay (p<0.0001). Conclusion: The prevalence of SUD in a community psychiatric setting is similar to that of in patients. Having a SUD is associated with poorer care outcomes
A research report submitted to the Faculty of Health Science, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Psychiatry